Planeación Financiera en la Empresa de Servicios Turísticos “Aguamania Cia. Ltda.” del cantón Catamayo. Periodos 2023 -2027. - Ordoñez Montalván, Verónica Jhuliana (2023)
The Curricular Integration Work entitled: Financial Planning in the Tourist Services Company "Aguamania Cia. Ltda." of the Catamayo canton. Periods 2023 -2027, was elaborated with the purpose of implementing the use of a financial tool, which serves as a contribution in the process of management decision making; improve the economic-financial situation and increase the profitability of the company in the coming years. To meet the objectives, the financial statements were compiled and through an unstructured interview with the manager and accountant, relevant information was obtained about the company, such as its characteristics, historical review, mission, vision, values, its main income-generating activities, structural organization chart and legal basis; a diagnosis was also made by applying financial indicators of liquidity, profitability, activity and indebtedness for the period 2021 and a SWOT matrix was prepared where the strengths, opportunities, weaknesses and threats were identified; Then the sales and purchase forecasts were prepared through the percentage increase method on a monthly basis, based on the sales and purchase history obtained for the year 2021 and with respect to the INEC Bulletin of Productive Figures for the year 2022, the average growth of the Accommodation and Food sector equivalent to 12.20%, which resulted in favorable increases, so that for the last projected year sales of $40. 965.02 and purchases of $6. 352.91, in this way a projected data base was generated in the cash inflow and outflow programs, in which 80% was considered cash and 20% credit, it should be emphasized that for the development of the cash outflow program with respect to expenses, it was considered, The increase in the unified basic salary specifically for salaries and other remunerations, social security contributions, employee benefit plans and fees, commissions and per diems to individuals and according to statistical data from INEC the inflation rate for the month of December 2022, which corresponds to 3.74% for other expenses in general; obtained the results, the cash budget was elaborated in order to foresee the future availability of money that the company will have, which shows surpluses, reaching the amount of $ 47. 428.44 in the year 2027, which can be reinvested for the benefit of the company for the implementation of new services and short-term investments that generate a financial return. Once the financial planning process was developed, the pro forma financial statements were prepared for the period 2023- 2027, in order to establish favorable estimates of assets, liabilities, equity, revenues, costs, expenses, and profit to provide a perspective of the future economic and financial situation to the managers; in addition, the Break-even Point was applied to the projected years, which allowed analyzing the relationship between costs, sales value and 5 profit to finally structure the Financial Planning report. In conclusion, this Curricular Integration Work served as an important contribution to the company and partners so that they can know the current economic-financial situation of the company, and at the same time establish corrective measures for improvement in terms of liquidity, indebtedness, activity and profitability; through financial planning, the company contributed to business development with information to project itself into the future in the achievement of its goals and objectives in the short and long term, having a clear vision of the expected financial position for the following years, and also served as a guide for the correct decision making, which will contribute to the strengthening and economic development, minimizing risk and taking advantage of opportunities.